Development of Urban Farming as a Strategy to Support Food Security - Hertati, Diana; Arif, Lukman; Nafi'ah, Binti Azizatun (MIMBAR : Jurnal Sosial dan Pembangunan, 2023)
Food security is a global strategic issue, affecting social and economic stability and even national security. Indonesia's population is increasing sharply, food security needs to be strengthened through urban farming. The source of food production in urban areas has decreased, due to the narrowing of agricultural land. The research method is descriptive and qualitative. Data collection was done using interview, observation and documentation techniques. The research analysis uses the model by Miles Huberman. The results of the study indicate that the community already understands and is familiar with urban farming with P2L, even groups of PKK women have participated in plant management in their yards; the inhibiting factors of the perpetrators are not understanding the technicalities of urban farming, lack of capital and the existence of extreme weather; The local government strongly supports the making of food security policies through urban farming by issuing several legal products of Regional Regulations.